Real-Life Analysis of Therapeutic Management and Its Correlation With the Dermatology Life Quality Index Score in 108 Patients With Pustular Psoriasis: An Italian Monocenter Study - Buononato, Dario; Scala, Emanuele; Benvenuto, Pierfrancesco; Caccavale, Stefano; Di Brizzi, Eugenia Veronica; Di Caprio, Roberta; Argenziano, Giuseppe; Balato, Anna (Dermatology Practical & Conceptual, 2025)
Introduction: Pustular psoriasis (PP) is a rare life-threatening skin disease with negatively impact on quality of life (QoL). Clinically, it may be systemic (generalized pustular psoriasis [GPP]) or localized on palms and soles (palmoplantar pustulosis [PPP]). It is not rare to observe plaque psoriasis associated with GPP. Objective: We explored the therapies used for PP and their correlation with patient QoL scores, through a cross-sectional study using retrospective data from a monocentric database in the period 2017-2021. Method: Patient characteristics were summarized using descriptive statistics and treatment predictors of QoL were identified by multiple regression analysis. Among 108 patients with PP, 57.4% had GPP + PSO whereas 42.6% had PPP. The therapeutic management is based on systemic conventional treatments and biological therapies in both GPP and PPP. Results: GPP + PSO patients with an impaired QoL (DLQI≥10) were associated with biological therapy including certolizumab (OR=2.38), etanercept (OR=2.25), secukinumab (OR=2.03) or ustekinumab (OR=2.79) whereas, PPP patients were positively associated with secukinumab (OR=2.85) or apremilast (OR 4.28, 95%-CI 0.56-9.62). Conclusion: Currently, systemic conventional therapy remains the therapeutic fulcrum of PP management. A great effect on QoL, especially for GPP+PSO, was assessed regardless the ongoing treatment and only newer biologic options were able to somehow positively impact.